Coronary Artery Bypass Grafting in Patients with Reduced Left Ventricular Myocardial Contractility - Yurii V. Kashchenko; Anatoliy V. Rudenko (Ukrainian Journal of Cardiovascular Surgery, 2024)
Coronary artery bypass grafting (CABG) is a crucial treatment for ischemic heart disease in patients with reduced left ventricular ejection fraction (LVEF). This approach improves survival and quality of life but carries a higher risk of complications. Off-pump CABG reduces the risk of strokes and bleeding, while on-pump CABG is beneficial for patients with complex anatomy. Planned use of cardiopulmonary bypass (CPB) stabilizes patients’ condition and reduces postoperative complications.The aim. To determine the optimal surgical strategy in patients with reduced LVEF and the reasons for emergency conversion to CPB.Materials and methods. The study included 210 patients with LVEF ≤ 35% who underwent CABG at the National Amosov Institute of Cardiovascular Surgery from January 1, 2015, to December 31, 2021. The patients were divided into three groups based on LVEF levels: 35–30%, 29–25%, and ≤ 24%. The frequency of elective and emergency CPB conversion was analyzed depending on LVEF. Postoperative complications and their frequency were also assessed based on the type of CPB conversion.Results. The study analyzed 210 patients with LVEF ≤ 35% who underwent CABG. The frequency of emergency CPB conversion increased as LVEF decreased, reaching 50% in patients with LVEF ≤ 24%. Planned use of CPB reduced the risk of postoperative heart failure.Conclusions. CABG is an effective treatment for ischemic heart disease in patients with reduced LVEF. Careful evaluation of preoperative and intraoperative factors is critical to minimizing complication risks.